Developing the optimal gross movement interventions to improve the physical fitness of 3–10 year-old children: a systematic review and meta-analysis - Hui, Li; Wei, Sun; Luping, Qu; Nannan, Guo (Frontiers in Psychology, 2024)
Objective: To identify the optimal parameters of gross movement interventions to yield the strongest effects on physical fitness among children aged 3-10 years and to provide a reference for the development of gross movement interventions to improve the physical fitness of children. Background: There has been a global decline in children's physical fitness. Previous studies have shown that gross movement interventions can improve children's physical fitness, but the optimal intervention parameters for achieving the strongest effects have yet to be determined. Therefore, we conducted this meta-analysis to determine the optimal intervention parameters for yielding the strongest effects on children's physical fitness. Methods: We searched the Web of Science, PubMed, China Biology Medicine, China National Knowledge Infrastructure, Wanfang Data, and China Science and Technology Journal databases to identify randomized controlled trials on the effects of gross movement interventions (walking, running, jumping, throwing, batting, rolling, spinning, catching, and leg lifting) on children's physical fitness (upper-body strength, lower-body strength, explosive power, speed, flexibility, and balance). We included studies published up to September 2023. The inclusion and exclusion criteria were developed based on the PICOS framework, and the quality of the included studies was evaluated. Subgroup analysis was performed using Review Manager 5.3, and the data were pooled using a random effects model to obtain the SMD (or WMD) and 95% CBM, CNKI, WanFang, and VIP 删除[李慧]: standardized mean differences (SMDs) 删除[李慧]: confidence intervals (CIs). Results: A total of 23 studies involving 2007 healthy children aged 3-10 years met the inclusion criteria. Gross movement interventions significantly improved the explosive power of children aged 3-10 years [WMD,6.2]. The most effective intervention duration was 16-18 weeks [WMD,0.45]. The most effective intervention frequency was one session per week [WMD,1.06]. The optimal duration of single sessions was 60 minutes [WMD,0.47]. Children aged 7-10 years [WMD, 1.41] showed the most significant improvements in physical fitness after gross movement interventions. Conclusion: Gross movement interventions had a positive effect on the physical fitness of children aged 3-10 years. The optimal intervention parameters include 60-minute sessions once a week across a total duration of 16-18 weeks.